King Boy of Brass - Alagoa, E J (Heinemann Educational Books Ltd, 1975)
King Boy brought the English Explorers,the Lander brothers,from Aboh to the Nun estuary in 1830.At last it became clear to the Europeans that the oil rivers formed the Delta of the Niger.
Keywords: Juvenile literature-Biographies (Amain (King Boy)-Nigeria-Historical-Colonial era-Non fiction-Nigeria (English)